A new insight into the mode of action between cement containing montmorillonite and polycarboxylate superplasticizer. Issue 4 (3rd April 2023) - Sha, Shengnan; Lei, Lei; Ma, Yihan; Jiao, Dengwu; Xiao, Zhiqiang; Shi, Caijun
Abstract : In this study, a PCE polymer was synthesized by copolymerizing isopentenyl polyoxyethylene ether (TPEG) with trans-2-butenedioic acid (FA). Thereafter, the dispersing effect of the resulting PCE polymer was evaluated via spread flow tests in cement pastes containing varying amounts of montmorillonite (MMT). The ultimate objective of this study was to investigate the mode of action between PCE polymer and MMT in cement paste and thus provide strategies to minimize the negative impact of MMT on PCE efficiency. The adsorbed amount of the PCE polymer linearly increased with the increasing dosage of MMT, whereas the spread flow of cement pastes linearly decreased with the increasing dosage of MMT. X-ray diffraction (XRD) results revealed that PCE/MMT ratio was critical in the sorption process, where electrostatic attraction played a significant role at low PCE/MMT ratios, whereas side chain intercalation dominated at high PCE/MMT ratios. The reduction in flowability caused by PCE is primarily attributed to the competitive adsorption of MMT in cement paste.